Words that Come Before All Else: An Embodied Decolonizing Praxis - Bensler, Heather; Scott Paul , Michelle (Witness: The Canadian Journal of Critical Nursing Discourse, 2025)
Abstract: In this article, we consider the communal practice of reading the Haudenosaunee Thanksgiving Address: Ohen:ton Karihwatehkwen as an entry point into anti-racism work in nursing education. We describe how this practice, inspired by Kimmerer’s (2013) Braiding sweetgrass: Indigenous wisdom, scientific knowledge and the teaching of plants, creates brave and generative spaces for students and educators to engage in difficult conversations about settler colonial violence and its ongoing impacts on Indigenous Peoples. We consider a broad theoretical overview of the history and practice of the Thanksgiving Address and how as a decolonizing practice, it works to counter the colonial logics that often dominate western academic institutions. The intentional and embodied practice teaches us about our kinship responsibilities, moves us toward a renewed relationship with the human and more-than-human world, cultivates gratitude, reciprocity, and a sense of belonging, and prepares us to engage in anti-racism work.